Evaluation groupware usability at the cognitive level of human action - Ferreira, António (2012)
This dissertation explores the importance of the cognitive level of human action in the evaluation and improvement of groupware usability. This research is motivated by the problem that current methods focus on the rational and social levels of human action and yet an increasing number of users relies on computers to fulfil collaborative tasks dominated by perceptual, cognitive, and motor skill. The first contribution of this research is a groupware interface model that leverages existing knowledge on cognitive-level behaviour with single-user interfaces by expanding its application to multi-user interfaces. To do this, I show that the key differences between users interacting with the computer and interacting with other users through the computer can be supported by specialised groupware information flows and input/output devices. The second contribution of this dissertation is a pair of methods for predicting groupware usability at the cognitive level of human action. The first method applies to scenarios of collaboration occurring routinely in shared workspaces. The second aims at capturing the intertwined nature of mixed-focus collaboration, encompassing shared and private workspaces. I use the methods to evaluate and compare the usability of competing designs in four scenarios of collaboration. The methods do not require user testing or functioning prototypes, so they can be integrated into the iterative process of interactive systems design. The third contribution of this research is the evaluation of an attentive electronic brainstorming tool, which implements a novel attentive device that adjusts the delivery of group awareness information according to users’ natural task switching between doing individual work and attending to the group. I present results from a laboratory experiment, which indicate that groups produced 9.6% more ideas when compared to the immediate broadcast of ideas and provide evidence suggesting that the usability improvement was due to the mitigation of information overload.